The relationship between teachers’ personality traits and job involvement: mediation of early maladaptive schemas - Akhtarinejad, Mehdi; Keshavarz, Samira; Moradialvand, Siros; Namjoo, Mahdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: One of the important substructures of this approach is the job attachment of employees, which appeared in scientific, commercial and psychological texts in recent years. Therefore, the present study was conducted to determine the mediating role of primary maladaptive schemas in the relationship between personality traits and job involvement of education teachers in Dehdasht city. Method: The method was descriptive-correlation type. The statistical population of this research was formed by all the teachers of Dehdasht city in 2022-2023. Among the statistical population, 120 people were selected and studied by purposive sampling method. To collect data, questionnaires of personality traits (NEO), Young’s maladaptive schemas (YSQ), and Edwards and Kilpatrick’s occupational attachment scale (1981) were used. After collecting and extracting data, participants’ scores were analyzed using multiple regression analysis and Bootstrap test. Results: The findings of the direct relationship paths of the research showed that there is a significant direct relationship between neuroticism, extroversion, openness to experience, conscientiousness and adaptability of personality traits with primary maladaptive schemas. There is a significant direct relationship between neuroticism, extroversion, openness to experience, conscientiousness and adaptability of personality traits with job attachment. Also, the results of the indirect relationship showed that personality traits have an effect on the job attachment of education teachers in Dehdasht city by mediating the initial incompatible schemas. Conclusion: Overall, the results showed that job attachment is affected by many factors, including personality traits and initial incompatible schemas.